2016
DOI: 10.1111/spol.12229
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Relations between English Students, Graduates Living at Home, and their Parents

Abstract: Debate about intergenerational relations has become more prominent since the financial crisis of 2007-09, focusing particularly on the difficulties faced by young adults trying to enter the labour and housing markets, whilst often bearing high levels of debt incurred as students. This article reviews the nature of the 'intergenerational contract' at both the micro level of the family, and at the macro level between individuals and the state. We then present qualitative, empirical data on the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Students from low income backgrounds, and those whose parents cannot provide the amount assumed by the assessed household contribution, “pay” for their financial self‐reliance by being tacitly excluded from the more expensive aspects of the student experience, taking on substantial amounts of part‐time work, or accessing further debt from private sources. In these terms, the article contributes to an emerging body of evidence that suggests changes in the funding of HE in England are, at a micro‐level, contributing to intra ‐generational inequalities in the form of both the costs and benefits of degree level study (Antonucci, ; Lewis & West, ).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Students from low income backgrounds, and those whose parents cannot provide the amount assumed by the assessed household contribution, “pay” for their financial self‐reliance by being tacitly excluded from the more expensive aspects of the student experience, taking on substantial amounts of part‐time work, or accessing further debt from private sources. In these terms, the article contributes to an emerging body of evidence that suggests changes in the funding of HE in England are, at a micro‐level, contributing to intra ‐generational inequalities in the form of both the costs and benefits of degree level study (Antonucci, ; Lewis & West, ).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Heath & Calvert (2013) points at several different forms of support next to 'earmarked' financial gifts or loans for a deposit or the co-signing of mortgage loans, such as: financial and in-kind contributions to offset general living expenses; overdraft and credit-card 'bail outs'; legacies from grandparents; or living in family members' 'buy-to-let' investment properties at reduced cost. Given the expense of private renting, for many young people co-residence in the parental home has furthermore become an important route to accumulate savings for a deposit (also see Lewis & West, 2016). For our hypotheses, we draw on theory and empirical findings that intergenerational support in general depends on two main factors: the ability to provide support, and the need for support (Fingerman et al, 2009;Henretta et al, 2002;Kalmijn, 2010;Kim et al, 2015;Spilerman, 2000).…”
Section: The Ability To Provide and The Need For Supportmentioning
confidence: 99%
“…Parents in social housing have lower incomes and less financial wealth by default. In a qualitative study of English highly educated parents and their student or graduated children, Lewis & West (2016) found that almost all parents felt an obligation to support their children financially if they were able to do so. However, there were considerable disparities in parents' abilities to provide support, with especially single mothers having difficulties making regular financial contributions to their children.…”
Section: The Ability To Provide and The Need For Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…In her seminal work on young people's housing in Scotland, England and Wales, Jones (1995) illustrated the importance of inter-generational relationships based on mutual trust and shared expectations about young people's changing needs during the transition to adulthood. Various studies show that these relationships form a basis upon which the ongoing provision (and acceptance) of parental support is actively and continuously negotiated, including after young people leave home (Clapham et al 2014;Jones 1995;Lewis and West 2016). Common reasons young Australians cite for remaining at home into adulthood, such as the ability to save money or the convenience and enjoyment of doing so (ABS 2009), are thus predicated on such relationships.…”
Section: Staying In or Leaving The Parental Homementioning
confidence: 99%